Mediation of Islamic Job Satisfaction on Organizational Determinants and Consequences Citizenship Behavior Evidence From Sharia Bank Medan - Rahmad Bahagia; Andri Soemitra; Zuhrinal.M. Nawawi (International Journal Of Economics Social And Technology, 2023)
Study This aims to test and analyze the influence of Quality Of Work Life and Perceived Organizational Support on Organizational Citizenship Behavior mediated by Job Satisfaction in a manner direct nor in a manner No direct. The approach used in the study This is the approach causal. Population in study This is a whole employee Indonesian Sharia Bank Medan City. Sample in study This use the formula slovin totaling 74 employees at Indonesian Sharia Bank Medan City. Deep data collection techniques study This uses technique documentation, observation, and questionnaire. Deep data analysis techniques study This use approach quantitative use analysis statistics using analysis test Outer Model, Inner Model Analysis, and Hypothesis Testing. Deep data processing study This using the PLS (Partial Leasre) software program. Research results This show that in a manner direct Quality Of Work Life, Perceived Organizational Support and Job Satisfaction have an effect significant to Organization Citizenship Behavior, Quality Of Work Life, Perceived Organizational Support influential significant to Job Satisfaction, in a No direct Quality Of Work Life and Perceived Organizational Support influential significant to Organizational Citizenship Behavior mediated by Job Satisfaction at Bank Syariah Indonesia in the city of Medan. For increased behavior ocb and satisfaction Work employees as well as support organization Indonesian Islamic bank employees in the city of Medan. Originality/value as far as the author know Still there is difference results in research conducted by researchers other